Meningkatkan Pemahaman Agama Melalui Pendampingan Ibu-Ibu di Dukuh Seglagah Desa Sempu - Dian Muzayyanatul Hasanah; Sri Ana (Social Science Academic, 2025)
Community in Seglagah hamlet, Sempu village, religious understanding among rural communities, especially mothers, needs continuous attention and improvement. The Community Service Program (KPM) provides an opportunity for Islamic Religious Education students to contribute to improving religious understanding in society. This study aims to analyze the role of KPM students in improving the religious understanding of mothers through routine recitation activities in Seglagah Hamlet, Sempu Village, Ponorogo Regency. This research uses a qualitative approach with field research methods through observation and interviews. The results showed that KPM students played a significant role in improving mothers' religious understanding through the delivery of charity materials during Friday recitation activities. The increase in religious understanding can be seen from the enthusiasm of mothers in participating in activities, asking questions about religious issues, and applying religious knowledge in daily life. The KPM program proves to be effective as a bridge between academic knowledge and community needs in the field of religious education.